2022
DOI: 10.53732/rccsociales/04.01.2022.65
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la pandemia del COVID-19 en el empleo y ventas de las MIPYMES de Paraguay

Abstract: Cómo referenciar este artículo/ How to reference this article Sánchez Báez, E. A., Ferrer Dávalos, R. M. y Sanabria, D. D. (2022). Impacto de la pandemia del COVID-19 en el empleo y ventas de las MIPYMES de Paraguay. Revista científica en ciencias sociales, 4(1), 65-77. RESUMENEl objetivo del estudio es determinar el impacto de la pandemia del COVID-19 en el empleo y ventas de las MIPYMES de Paraguay. Se utilizó un enfoque cuantitativo, transeccional de tipo descriptivo con un muestreo estratificado. Se realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Those with flourishing mental health also reported that work was the greatest source of stress. We might consider that after 4 years of COVID-19 pandemic, people still experience difficulties in their financial affairs (Center on Budget and Policy Priorities, 2020; Sánchez Báez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Those with flourishing mental health also reported that work was the greatest source of stress. We might consider that after 4 years of COVID-19 pandemic, people still experience difficulties in their financial affairs (Center on Budget and Policy Priorities, 2020; Sánchez Báez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Partial or total blockages in their operations have led in many cases to the definitive closure of several ventures, a change of line of business, or a change of business model (Burhan Ismael et al, 2021). This situation has worsened in developing countries such as Paraguay, where on the one hand the limited action of governments and on the other hand the poor quality of the business fabric have had, to a certain extent, an impact on the ability to successfully face this type of crisis (Sánchez-Báez & Sanabria, 2019). In this sense, although most Ibero-American governments have implemented support strategies for MSMEs, it seems that these were poorly designed since they had very little effect on mitigating the loss of income for them (García-Pérez- de-Lema et al, 2021;Sánchez-Báez et al, 2021;Ferrer Dávalos, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this article tries to fill the information gap on Paraguayan MSMEs by providing some evidence related to the operations of these companies and the way they have faced the pandemic, since they represent 97% of the productive units in the country and generate approximately 61% of employment (MIC, 2019). Some studies show that the operational capacity of Paraguayan MSMEs and therefore their capacity to generate and maintain jobs has been negatively impacted by the pandemic (Sánchez-Báez et al, 2022). Therefore, taking into account the multiple effects of COVID-19 on businesses, this article studies some organizational characteristics that in some way could have impacted the sales of Paraguayan MSMEs during the pandemic and aims to report what happened in these firms in relation to supplier and supply chain relationships and how sales were affected during this period.…”
Section: Introductionmentioning
confidence: 99%